Effects of Yeast Strain and Juice Nitrogen Status on Glutathione Utilisation during Fermentation of Model Media - Marlize Z. Bekker; Kathleen M. Cuijvers; Allie C. Kulcsar; Ross D. Sanders; Dimitra L. Capone; David W. Jeffery; Simon A. Schmidt (Australian Journal of Grape and Wine Research)
Background and Aims. An OIV resolution provides guidelines on using glutathione as a prefermentation additive when the amount of yeast assimilable nitrogen (YAN) of a juice or must is adequate, to avoid the metabolism of glutathione by the yeast. The effect of YAN concentration on glutathione metabolism by yeast had not been determined. This study explored whether nitrogen management could be used to control glutathione consumption during fermentation. Methods and Results. An HPLC-UV method was developed to quantify reduced L-glutathione (GSH) and oxidised glutathione (GSSG) and used to monitor yeast GSH metabolism during alcoholic fermentation with two yeast strains (AWRI 1688 and AWRI 2861). The addition of GSH had no impact on the fermentation rate of the chemically defined medium, even in a limited YAN environment; however, a decrease in glutathione concentration occurred regardless of YAN concentration. The effect of GSH on volatile sulfur compound formation was yeast strain-dependent. Conclusions. Increasing the YAN status of a chemically defined medium led to a decrease in GSH consumption during fermentation, but the loss of GSH could not be prevented entirely, even with a low initial GSH concentration and high initial YAN. Significance of the Study. In the presence of higher concentrations of GSH during fermentation, there is a risk of forming undesirable fermentative sulfur compounds that are not mitigated through nitrogen supplementation. Thus, it seems unlikely that an argument could be made for the inclusion of GSH in relevant food standards codes as a wine additive especially if a lack of GSH metabolism was a criterion.